Toward a unified taxonomy of Niphargus (Crustacea: Amphipoda): a review of morphological variability - Fišer, Cene; Trontelj, Peter; Luštrik, Roman; Sket, Boris (Zootaxa, 2009)
Niphargus is the largest genus of freshwater amphipods, burdened with problematic and largely incomplete taxonomy. This paper is an overview of the morphological characters relevant for niphargid taxonomy, and is conceived as an early step toward a unified taxonomy in the emerging era of cyber-taxonomy. The core element is a taxonomic on-line revision system based on a continuously updated, peer-reviewed and freely accessible morpho-databases (see for example http:// niphargus.info/) that would provide a source of data necessary for comparisons of taxa, generation of species descriptions, and testing phylogenetic hypotheses. In Niphargus, the coding of morphological variability is not straightforward. Several characters are continuous, polymorphic, or subject to allometric growth. We here present a detailed overview of published and new characters together with their variability levels, and describe how the characters are measured and quantified.